Fetomaternal outcome in caesarean section at full dilatation - Gupta, Kavita; Garg, Apurva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To study indications, intraoperative and postoperative complications and fetomaternal outcome in cesarean sections done at full dilatation. Methods: This is a prospective cross-sectional study which was conducted in the department of obstetrics and gynecology, RNT medical college, Udaipur from November 2018 to April 2019. 100 cases of caesarean sections at full dilatation which were performed during this period were analyzed for indications and maternal and fetal morbidity. Results: Among these 100 cesarean sections, majority of cases were in the age group of 21-30 years (46%), booked and Primigravida(81%).Most common indications were cephalo-pelvic disproportion (27%) and fetal distress (21%). Most commonly baby was delivered either by vertex (44%) or by Patwardhan (31%). Intraoperative complications were higher in terms of hematuria in 41%, Atonic PPH in 35%, uterine incision extension in 28% of cases. In one case bladder injury was noticed. Increased incidence of post-operative febrile illness and wound infection were noted. 44% baby’s required nursery admission, most commonly due to birth asphyxia (16%) and RDS (11%). Conclusions: Cesarean section in the 2nd stage of labor is associated with significantly increased maternal morbidity, Neonatal morbidity and mortality. So proper monitoring during labor and involvement of skilled obstetrician in decision making and delivery is crucial to minimize fetomaternal complications.